What we mean by the American dream : stories we tell about meritocracy - Taussig, Doron (ILR press, an imprint of Cornell University Press, 2021)
"Do we live in a meritocracy? Many believe we do and that it is an essential element of the American Dream. Others would say we do not. In this book, Doron Taussig examines how people think about the relationship between merit and achievement. The surprise is that our understanding of how life works and what it means to deserve something is more flexible and fluid than our mythology"